Metamemory that matters: judgments of importance can engage responsible remembering. Issue 3 (16th March 2021) - Murphy, Dillon H.; Castel, Alan D.
ABSTRACT: Adaptive memory refers to the memory advantage for information processed in a survival and/or reproduction context while metacognition involves the awareness of what we can later remember. The notion of "responsible remembering" captures how memory functions to prioritise important information that will need to be remembered and how metacognitive processes may be more precise in situations involving consequences for forgetting. In 5 experiments, we examined whether judgments of learning and judgments of importance affect recall selectivity for information with negative consequences if forgotten. We presented participants with lists of children, each with 2 foods they like, 2 foods they dislike, and 2 foods they are allergic to. When making no metacognitive judgments or making JOLs for each food preference, participants best recalled foods the children liked, likely resulting from serial remembering (recalling information according to where it was presented). However, when judging the importance of remembering items, participants were strategic in their memory for the food preferences such that they best recalled information they rated as important to remember (allergies). These results suggest that when forced to consider the importance of remembering, participants engage in responsible remembering by deeming information with consequences for forgetting as most important and subsequently best remembering this information.